2017
DOI: 10.15171/ijb.1541
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Recombinant Strain of Cucurbit Aphid Borne Yellows Virus in Iran

Abstract: (CABYV) is among the most important yellowing viruses on cucurbits in Iran. The presence of CABYV has been previously reported from the major cucurbit growing areas in Iran, however, there are few studies concerning the detection of the different strains of this virus in the grower's fields, and especially, there is no report of the weed host plants near crop fields. This study was done in order to detect the new strains of the CABYV polerovirus in cucurbits and the weed plants in the Lorestan province, Iran, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Moreover, plant viruses can emerge in crops from reservoir wild plant hosts in which they are often asymptomatic. Spread from the reservoirs into a new environment with the establishment of productive infections and effective between-host transmission mechanism are steps that require emergence to occur [ 10 ]. In addition, many wild plants appear to have multiple infections, including both acute and persistent viruses [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, plant viruses can emerge in crops from reservoir wild plant hosts in which they are often asymptomatic. Spread from the reservoirs into a new environment with the establishment of productive infections and effective between-host transmission mechanism are steps that require emergence to occur [ 10 ]. In addition, many wild plants appear to have multiple infections, including both acute and persistent viruses [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…CABMV can infect plants of the families Passifloraceae, Fabaceae, Cucurbitaceae, Solanaceae, Chenopodiaceae, Amaranthaceae, and Poaceae [ 50 , 51 , 52 , 53 ]. CABYV has a wide range of Cucurbitacea plants as hosts and can infect several other plant families, such as Brassicaceae, Asteraceae, Malvaceae, Fabaceae, Amaranthaceae, Chenopodiaceae, Papaveraceae, Lamiaceae, Portulacaceae, Solanaceae, and Passifloraceae [ 16 , 17 , 20 , 27 , 32 , 54 , 55 , 56 , 57 , 58 ]. However, CABYV infection in Macroptilium spp., Stylosanthes spp., Sida spp., and Bignonia spp., as well as CABMV infection in Sida spp.…”
Section: Resultsmentioning
confidence: 99%
“…Building upon a previous research which identified WMV from bitter apple plants in the Jiroft region, our study aimed to explore a wider range of potential viruses in bitter apple plants showing viral symptoms in the Jiroft region. In addition to WMV, other studies in Iran have detected the presence of Papaya ring spot virus-type W and cucurbit aphid-borne yellows virus in this plant [ 4 5 ]. These findings indicate that this plant species can act as a viral reservoir affecting agricultural crops [ 4 8 ].…”
Section: Discussionmentioning
confidence: 99%